Savings externalities and wealth inequality - Konstantinos Angelopoulos; Spyridon Lazarakis; Jim Malley (Center for Economic Studies and ifo Institute (CESifo), 2019)
Incomplete markets models imply heterogeneous household savings behaviour which in turn generates pecuniary externalities via the interest rate. Conditional on differences in the processes determining household earnings for distinct groups in the population, these savings externalities may contribute to inequality. Working with an open economy heterogenous agent model, where the interest rate only partially responds to domestic asset supply, we find that differences in the earnings processes of British households with university and non-university educated heads entail savings externalities that increase wealth inequality between the groups and within the group of the non-university educated households. We further find that while the inefficiency effects of these externalities are quantitatively small, the distributional effects are sizeable.
Keywords: E21; E25; H23; 330; incomplete markets; productivity differences; savings externalities